PRESUPPOSITIONS IN GREEN CAMPAIGN STICKERS ISSUED BY INTERNATIONAL ASSOCIATION OF STUDENTS IN AGRICULTURE AND RELATED SCIENCES OF UNIVERSITAS BRAWIJAYA - ALFANI, FAHMI REZA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: presupposition, presupposition trigger, pragmatic presupposition.Presupposition is an important element in a communication process. It is defined as the common knowledge belonging to the speaker. Presupposition could be identified by two ways; presupposition trigger referring to the triggered word in a utterance or written expression, and pragmatic presupposition referring to presupposition which is made by considering the speaker as the one producing the utterance or written expression. Presupposition can be found in daily communication such as, in the campaign. In this study, the writer analyzes presupposition within written expression of the green campaign stickers on IAAS Universitas Brawijaya. There are two problems to be solved, namely (1) What are the presupposition triggers of the written expression used in green campaign stickers of International Association of Students in Agriculture and Related Sciences ‘IAAS’ Universitas Brawijaya? and (2) What are the pragmatic presupposition of the written expression used in green campaign stickers ofInternational Association of Students in Agriculture and Related Sciences ‘IAAS’Universitas Brawijaya?.This study used qualitative approach in document analysis since it focused on analyzing the written expression in the campaign. The data were collected from the green campaign stickers in IAAS Universitas Brawijaya when the stickers were distributed in Car Free Day Malang on Sunday, September 23, 2012. Then, data were analyzed by using Levinson’s theory of presupposition trigger (1983) and Karttunen and Stalnaker’s theory of strategy of pragmatic presupposition (1974).Definite description, change of state verb, question, temporal clasuse, iterative, contrast and comparison, and counter factual condition were categories of presupposition trigger found in the written expressions of 7 green campaign stickers. Then, the result of presupposition triggers became a reference to construct pragmatic presupposition in the written expression of green campaign stickers.The writer suggests the sticker makers make effective and good media. This study is also suggested for the students of linguistics to use this study as an example of presupposition used in mass media. It is also suggested for the next researchers that this study can be used as a reference in the same topic.